2023
DOI: 10.3390/ijerph20020916
|View full text |Cite
|
Sign up to set email alerts
|

Do Determinants of Quality of Life Differ in Older People Living in the Community and Nursing Homes?

Abstract: Objectives: The aim of the present study was to examine and compare the relationship between nutritional status, physical activity (PA) level, concomitant chronic diseases, and quality of life (QoL) in community-dwelling (CD) older people and nursing home (NH) residents. Material and Methods: One hundred NH residents aged 60 years and above and one hundred sex- and age-matched CD older adults were examined. The QoL was examined with the EuroQol-5D questionnaire. Nutritional status was assessed with the Mini Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The determinants of malnutrition are especially important in the most vulnerable older population, with the risk of naturally developing general poor health or chronic diseases [ 8 ]. Some of these factors could be potentially influenced by the environment of the geriatric population, which has been shown to have a significant impact on nutrition [ 9 ]. If an older person is residing in a hospital or long-term care facility, it has been shown that they are more likely to have a poor nutrition status compared to a community-dwelling older person [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The determinants of malnutrition are especially important in the most vulnerable older population, with the risk of naturally developing general poor health or chronic diseases [ 8 ]. Some of these factors could be potentially influenced by the environment of the geriatric population, which has been shown to have a significant impact on nutrition [ 9 ]. If an older person is residing in a hospital or long-term care facility, it has been shown that they are more likely to have a poor nutrition status compared to a community-dwelling older person [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that low levels of physical and cognitive, being overweight or obese body mass index (BMI), and also physically inactive were related to poor quality of life (QoL) amongst home-dwelling older people (7)(8)(9)(10). Meanwhile, concomitant diseases played an essential role in determining QoL status amongst institutionalised older people (11).…”
Section: Introductionmentioning
confidence: 99%